Non-thermal plasma couples oxidative stress to trail sensitization through dr5 upregulation - Hwang, Soon Young; Nguyen, Ngoc Hoan; Kim, Tae Jung; Lee, Youngsoo; Kang, Mi Ae; Lee, Jong Soo (International Journal of Molecular Sciences, 2020)
Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) induces apoptosis in various tumor cells without affecting most normal cells. Despite being in clinical testing, novel strategies to induce TRAIL-mediated apoptosis are in need to overcome cancer cell unresponsiveness and resistance. Plasma-activated medium (PAM) markedly stimulates reactive oxygen/nitrogen species (ROS/RNS)-dependent apoptosis in cancer cells. We investigate the capability of PAM and TRAIL (PAM/TRAIL) combination therapy to overcome TRAIL resistance and improve the anticancer efficacy of TRAIL. The combinatorial treatment of PAM and TRAIL shows synergistic effects on growth inhibition in TRAIL-resistant cancer cells via augmented apoptosis by two attributes. DR5 (TRAIL-R2) transcription by CHOP is upregulated in a PAM-generated ROS/RNS-dependent manner, and PAM itself upregulates PTEN expression mediated by suppression of miR-425 which is involved in Akt inactivation, leading to increased apoptosis induction. Treatment of cancer cell lines with the antioxidant N-acetylcysteine reduces the extent of membrane dysfunction and the expression of both CHOP-DR5 and miR-425-PTEN axes, attenuating PAM/TRAIL-induced cancer cell apoptosis. These data suggest that PAM/TRAIL treatment is a novel approach to sensitizing cancer cells to TRAIL-induced apoptosis and overcoming TRAIL resistance. PAM is a promising candidate for further investigations as a chemotherapeutic sensitizer in the treatment of cancer.
Keywords: A549 Cells; Apoptosis; Gene Expression Regulation, Neoplastic; HeLa Cells; Hep G2 Cells; Humans; MicroRNAs; Neoplasm Proteins; Neoplasms; Oxidative Stress; Plasma Gases; Receptors, TNF-Related Apoptosis-Inducing Ligand; RNA, Neoplasm; Signal Transduction; TNF-Related Apoptosis-Inducing Ligand; Up-Regulation; Apoptosis; DR5; Plasma-activated medium; ROS/RNS; TRAIL